Efficacy and safety of tranexamic acid for patients with intertrochanteric fractures treated with intramedullary fixation: A systematic review and meta-analysis of current evidence in randomized controlled trials - Jiang, Jiabao; Xing, Fei; Zhe, Man; Luo, Rong; Xu, Jiawei; Duan, Xin; Xiang, Zhou (Frontiers in Pharmacology, 2022)
Background: Tranexamic acid (TXA) has been widely applied to reduce perioperative bleeding. Recently, several studies focused on the administration of TXA in the treatment for with intertrochanteric fracture patients treated with intramedullary fixation. However, the efficacy and safety of TXA in these studies remain controversial. Therefore, we performed this systematic review and meta-analysis to investigate the efficacy and safety of TXA in intertrochanteric fracture patients treated with intramedullary fixation. Methods: We systematically searched electronic databases, including Cochrane, PubMed, and EMBASE, up to May 16, 2022. The efficacy and safety of TXA was evaluated in four aspects, which were bleeding-related outcomes, non-bleeding-related outcomes, thromboembolic events, and other complications. The outcomes of these studies were extracted and analyzed by RevMan Manager 5.4. Results: Finally, nine randomized controlled trials, involving nine hundred and seventy-two intertrochanteric fracture patients treated with TXA, were enrolled in this study. In the bleeding-related outcomes, TXA group was significantly lower than the control group in terms of total blood loss (MD=-219.42; 95% CI, -299.80 to -139.03; P <0.001), intraoperative blood loss (MD=-36.81; 95% CI, -54.21 to -19.41; P <0.001), hidden blood loss (MD=-189.23; 95% CI, -274.92 to -103.54; P<0.001), and transfusion rate (RR=0.64; 95% CI, 0.49 to 0.85; P =0.002). Moreover, the postoperative hemoglobin on day 3 of the TXA group was significantly higher than that of the control group (MD=5.75; 95% CI, 1.26 to 10.23; P =0.01). In the non-bleeding-related outcomes, the length of hospital stays was significantly shorter in the TXA group (MD=-0.67; 95% CI, -1.12 to -0.23; P =0.003). In terms of thromboembolic events, there was no significant differences between the TXA group and control group in deep vein thrombosis, pulmonary embolism, myocardial infarction, and ischemic stroke. As for complications and mortality, there was no significant differences between the TXA group and control group in respiratory infection, renal failure, and postoperative mortality within one year. Conclusion: TXA is an effective and safe drug for perioperative bleeding control in intertrochanteric fracture patients treated with intramedullary fixation. However, the long-term efficacy of TXA still needs to be investigated by large-scale multicenter randomized controlled trials.